An apophatic response to the evidential argument from evil - Brown, Joshua Matthan (International journal of philosophy and theology, 2017)
I argue that Christian apophaticism provides the most powerful and economical response to the evidential argument from evil for the non-existence of God. I also reply to the objection that Christian apophaticism is incoherent, because it appears to entail the truth of the following contradiction: it is both possible and impossible to know God’s essential properties. To meet this objection, I outline a coherent account of the divine attributes inspired by the theology of the Greek Father’s and St. Gregory Palamas.